The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1983
DOI: 10.1080/00268948308072454
|View full text |Cite
|
Sign up to set email alerts
|

Zvetkow Twist Viscosity Measurements of Some Nematic Liquid Crystals

Abstract: Zvetkow twist viscosity measurements are reported for a series of cyanobiphenyl liquid crystals and their cutectic mixtures in the nematic phase. The values obtained exhibit a n odd-even variation. If the data are plotted against a reduced density, they divide into two groups, one corresponding to the odd and the other to the even series. This is attributed to effects of the configuration of the alkyl chain on the molecular packing density in the nematic phase. Using the Maier-Saupe theory, interaction energie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 20 publications
5
13
0
Order By: Relevance
“…Close agreement is observed between the measurements reported in this paper and those of Seidler et al [14] at the highest temperatures, but significant differences are observed as the temperature is lowered. Torsion angle [16]; -Seidler et al [14]; X Beens [17].…”
Section: Temperature-dependent Density Measurementssupporting
confidence: 90%
See 2 more Smart Citations
“…Close agreement is observed between the measurements reported in this paper and those of Seidler et al [14] at the highest temperatures, but significant differences are observed as the temperature is lowered. Torsion angle [16]; -Seidler et al [14]; X Beens [17].…”
Section: Temperature-dependent Density Measurementssupporting
confidence: 90%
“…The constants obtained from the fitting of the data to Equation (3) are listed in Table 2 3.2 Viscosity coefficient measurements The principle viscosity coefficients; η 1 , η 2 , η 3, and η 45 were measured for all the liquid crystal materials using the oscillating plate viscometer method (OPV) following the procedures outlined in the previous paper [1]. The rotational viscosity coefficients γ 1 were measured using a modified version of the method described by Seidler et al [14] and described in the previous paper [1]. In this experiment the magnetic field is rotated relative to the suspended sample.…”
Section: Temperature-dependent Density Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerical calculations are performed with the parameters of the liquid-crystal mixture E7 from Merck, listed in Table I [17], [22]. …”
Section: Simulation Resultsmentioning
confidence: 99%
“…However, because of the scatter in the values for elastic constant K reported in literature [41][42][43][44] only rough estimation can be made. For the typical average value K = 1 • 10-" N and with (Av) = 15 kHz and i = 0.1 Pa • s [42,[45][46][47][48] one obtains A = 2.0. 104 s -312 in agreement with experiment.…”
Section: Bulk 5cbmentioning
confidence: 99%